Crustal inhomogeneities of Bransfield Strait (West Antarctiсa). New geophysical data - Levashov, S.; Korchagin, I.; Kozlenko, Yu.; Solovyov, V. (Український антарктичний журнал, 2006)
The Ukrainian Antarctic expeditions provided new geophysical data for many West Antarctica bottom structures. Gravity, magnetic- and electromagnetic surveys near the Antarctic Peninsula enabled to specify the age of the formation of some blocks, separate local crustal inhomogeneities of Bransfield Strait and continental margin of Antarctica. The similar results obtained by three different methods assure the notable magmatic activity of Bransfield Trough that forms in the conditions of structural transformations and rifting processes migrating NE-SW war along Bransfield Strait. It is quite probable that this area is dominated by diffusion tension process but not by the expansion of a mid-oceanic ridge in a back of a volcanic arc. Получены новые данные о распределении геофизических полей для тектонических структур дна Западной Антарктики, которые позволили выделить локальные неоднородности земной коры пролива Брансфилд. Выявлено большое влияние тектонических факторов на формирование неоднородной осадочной толщи и основных характеристик глубинных разрезов земной коры. Распределение аномальных магнитовозмущающих тел в верхних частях аномальной коры в значительной мере отражает наличие силлов и отдельных интрузий, выделенных по данным вертикального электрорезонансного зондирования. Отриманo нові дані про розподіл геофізичних полів для тектонічних структур дна Західної Антарктики, які дозволили виділити локальні неоднорідності земної кори протоки Брансфілд. Виявлено великий вплив тектонічних факторів на формування неоднорідної осадової товщі. Показано, що розподіл аномальних магнітозбурюючих тіл має такий саме характер, як і розташування силлів, визначених методом вертикального електрорезонансного зондування.